Respiratory Microbial Co-infection With SARS-CoV-2 - Massey, Bill W.; Jayathilake, Karuna; Meltzer, Herbert Y. (Frontiers in Microbiology, 2020)
Co-infection with additional pathogens is a well-known feature of pandemics. We determined the prevalence and type of a wide variety of respiratory pathogens in 12,075 United States subjects tested for SARS-CoV-2 infection in March and April 2020. Infections with other respiratory pathogens, which on their own produce at least some SARS-CoV-2 symptoms including mortality, were present in both SARS-CoV-2 + and SARS-CoV-2- subjects. Non-SARS-CoV-2 infection rates were significantly higher in SARS-CoV-2 + (86%) patients than SARS-CoV-2– patients (76%) (p < 0.0001). Among the co-pathogens present in both subject groups were K. pneumoniae and M. catarrhalis which can produce serious respiratory illness on their own, Advanced age and nursing home status were associated with higher SARS-CoV-2 + and co-infection rates. Testing for the presence of co-pathogens going forward will assist in the diagnosis and optimal treatment of suspected SARS-CoV-2 respiratory infections in the current pandemic.